David goes to school - Shannon, David, 1959- (New York : Scholastic Inc., 2000)
David's activities in school include chewing gum, talking out of turn, and engaging in a food fight, causing his teacher to say over and over, "No, David!"
"Originally published in hardcover by the Blue Sky Press in 1999"--T.p. verso.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Keywords: Behavior -- Fiction; Schools -- Fiction